1946, Last war of independence: royal Indian navy mutiny - Kapoor, Pramod (New Delhi Lotus collection, 2022)
This book is about In 1946, 20,000 non-commissioned sailors of the Royal Indian Navy mutinied.
Keywords: Indian Navy